THE IMPACT ANALYSIS OF COORDINATION AGAINST THE EFFECTIVENESS OF SERVICE ONE-STOP CORPORATE ADMINISTRATION SYSTEM AREA AT PANDEGLANG, BANTEN PROVINCE - Lia Muliawaty - (Lembaga Penelitian Universitas Pasundan, 2017)
The main problem in this research is the effectiveness of the service of motor vehicle registration number at the offices of Single Administrative System Single Roof Pandeglang Banten Province low, allegedly caused by the coordination between each unit or part has not run optimally. The method used in this research is descriptive analysis by using path analysis (path analysis) that is by seeing how big influence and independent variable to dependent variable, either influence directly or indirect influence. With this design will be measured directly or indirectly the coordination influence expressed in 7 (seven) dimensions, namely the existence of agreement and unity of understanding, the existence of agreement on the activities, the existence of obedience, the exchange of information, the presence of coordinators who can lead, the existence of information from Various parties, and the mutual respect for the effectiveness of service at the Office of Pandeglang Area Manunggal One Roof Administration System of Banten Province.The results of the research can be found that the effectiveness of Motor Vehicle Tax Service is influenced by the coordination at the office of Pandeglang Area Manunggal One Roof Administration System of Banten Province, with the percentage is 98.0%. This means that the coordination is very dominant and decisive towards the increase of tax service on the Pandeglang Area Manunggal One Roof Administration System of Banten Province. However there are also other factors that are not examined (epsilon) but determine against the tax service on Pandeglang Area Manunggal One Roof Administration System of Banten Province of 2.0%.